Use of video modelling to teach complex and meaningful job skills to an adult with autism spectrum disorder. (3rd July 2016) - Rausa, Vanessa C.; Moore, Dennis W.; Anderson, Angelika
Abstract: Objective : To examine the effectiveness of a video modelling (VM) intervention to teach job-related telephone skills to an adult with Autism Spectrum Disorder (ASD). Methods : A multiple baseline design across four telephone-relevant behaviours was used to assess the effects of the intervention on the participant's ability to respond to telephone calls. Results : Use of the VM intervention led to immediate improvements in listening and responding to both orders and complaints; more gradual improvements were also observed in the participant's professional speech. All skill increases were maintained at follow-up. Conclusion : VM may be an effective method of teaching complex vocational skills to adults with ASD, although a stronger focus on social skills may be warranted in the future.